Isolation and Characterization of Fesoterodine Fumarate Related Impurity - Rajput, A.P.; C. Sonanis, Manohar (Asian Journal of Chemistry, 2013)
During analytical method for the determination of related substances of fesoterodine fumarate using RP-HPLC, one unknown impurity was observed more than 0.1 % level and also keeps on increasing in forced degradation study. Hence it was desirable to isolate, identify and characterize this impurity using advanced analytical techniques. A simple, sensitive and specific RP-HPLC method was developed for the quantification of related impurities of fesoterodine fumarate. The chromatographic separation was accomplished on a YMC Pak ODS-A (150 mm × 4.6 mm), 5 μ column using mobile phase system with gradient elution of solvent-A (0.1 % trifluro acetic acid in water and methanol in the ratio of 70:30 v/v) and solvent-B (acetonitrile). The analytes were detected at 215 nm using photo diode-array (PDA) detector. The investigated impurity has been isolated using preparative RP-HPLC method using YMC Pak ODS-A (250 mm × 50 mm) 12 μ. Then the isolated impurity was identified and characterized.